On target? The incidence of sanctions across listed firms in Iran - Mirko Draca; Jason Garred; Leanne Stickland; Nele Warrinnie (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2019)
How successful are sanctions at targeting the economic interests of political elites in affected countries? We study the efficacy of targeting in the case of Iran, using information on the stock exchange-listed assets of two specific political entities with substantial influence over the direction of Iran's nuclear program. Our identification strategy focuses on the process of negotiations for sanctions removal, examining which interests benefit most from news about diplomatic progress. We find that the stock returns of firms owned by targeted political elites respond especially sharply to such news, though other listed firms unconnected to these elites also benefit from progress towards sanctions relief. These results indicate the 'bluntness' of sanctions on Iran, but also provide evidence of their effectiveness in generating economic incentives for elite policymakers to negotiate a deal for sanctions relief.
Keywords: F51; 330